EUROPEAN CROSS-BORDER ASSOCIATIONS: ON THE SOCIAL FUNCTION OF LAW - Justyna Dąbrowska (Zeszyty Prawnicze)
The aim of this article is to answer the question of the potential eﬀectiveness of introducing the regulation on European cross-border associations (ECBAs) into the national legal systems of EU Member States. The goal of this initiative is to facilitate the cross-border activities of non-profit associations in the European Union, with the aim of improving the operation of the internal market by removing legal and administrative barriers and levelling the playing field for non-profit associations which operate or wish to operate in more than one Member State, thereby promoting the role that non-profit associations play in generating economic and social value in the EU. In its first part, the article discusses the origins of the European Commission’s proposal and presents the proposed structure and principles of operation of the ECB. In the second part, the article contains conclusions and doubts concerning the Commission’s proposal, also referring to the Polish legal regulations relating to associations and legal solutions operating in other EU countries. Rather than systematically or thoroughly discussing association law in the EU, the article intends to address certain elements of the proposed Directive, but above all to contribute to a doctrinal discussion on this subject, including how research on European cross-border associations should be conducted. I use the example of the planned regulation to illustrate the question of the impact of the law as a carrier of value in bringing about the expected social changes. I focus my considerations on the concept of the law’s social function to ensure legal eﬀectiveness. However, eﬀectiveness should not be understood as compliance of the social results of a set of legal norms with the legislator’s intentions, but instead as the situation when the law is well embedded institutionally and leads to an increase in social and individual utility.